The hospital almoner - Maule, Lilian A. (London : Kegan Paul, Trench, Trubner & Co.)
1904-09 1904 1900s 2 pages : illustrations 2 OUR HOSPITALS AND CHARITIES and the greatest accuracy, and the case treated on its merits. A talk with Miss Mudd at St. George's, or Miss Nussey at Westminster, will speedily convince the unbelieving that "hardness" is not a feature of their work. On the contrary, they will show you that the mere elimination of unsuitable cases is one part only of that work, and by no means the most important. Numberless are the instances in which, by following up a case, ordered, let us say, some special course of treatment, or some appliance necessitating time and trouble to procure, the almoner has been able to put such a patient into communication with the Surgical Aid Society, or some other agency, or to call the attention of the district nurse or the parish clergy to a ease requiring home treatment or change to a Convalescent Home. The almoner's visits to the homes of patients, or the visits of the C.O.S. workers, whose co-operation is part of the scheme, may bring to light a case for the Society for the Prevention of Cruelty to Children, or may lead to the handing over of a patient to the Poor Law Infirmary ; in fact, the great object is, not to be "down upon" those who apply to the hospitals, but to see to it that each person needing treatment or advice shall ultimately be dealt with by that particular institution most suitable to his or her needs. Another very important aspect of the almoner's work must not be overlooked. It is for them to induce those who can afford it to keep up their payments to sick clubs and provident dispensaries, and to encourage them to pay for surgical appliances, &c. Experience shows that flagrant abuse of hospital privileges is more rare than might be expected, and where it does exist ignorance more than intentional deceit is often the cause. A "loan system" to help patients to procure appliances ordered by the doctors has proved successful, bad debts being exceedingly few in number, for the sums advanced are almost invariably paid back in small weekly amounts. Naturally it is of the first importance that almoners shall be carefully selected. Only those women should take up this calling who are keenly interested in it for its own sake, and they must be prepared to devote probably a year to the training which is an essential qualification. It is work for which women are especially fitted, for enthusiasm is needed, untiring attention to detail, and great tact. It is widely recognized that the methods upon which the out-patient departments at many of the large general hospitals are at present administered are doing infinite and far-reaching harm, for the question has to be considered from the broad social standpoint, not merely from the narrower one of the philanthropist, who often does not look beyond the immediate relief of suffering. Some hospital administrators aim at the pockets of the charitable by piling up the number of cases treated at their particular institution in a year, and this extraordinary ambition to outbid each other in the yearly sum total of patients is doubtless the reason why the hospitals are backward in grappling practically with the out-patient difficulty. Patients and doctors are alike suffering from the congested state of the out-patient rooms, which as pauperizing agencies, militating against habits of thrift and self-reliance, are really becoming a grave social danger to the community at large. If no effort is made to discriminate between the claims of those who apply for relief, it cannot be considered surprising if the people come to regard it as a right, and cease to make provision for sickness or accident. If the almoner system became more general, with its main feature of co-operation between hospital officers and outside agencies, a great step in the right direction would be made. The mere institution of so-called "inquiry officers" working independently on different lines, with no organized inter-communication, will not do much towards the reform which is needed. The "expense" of a highly trained officer is the objection generally raised by hospital committees and secretaries. But efficiency in administration tends in the long run towards economy. LILIAN A. MAULE. The new clubs opened at Bordon and Longmoor Camps by the Church of England SOLDIERS' AND SAILORS' CLUBS Committee fill a long-felt want. There is, however, still a liability of £700. The CHURCH OF ENGLAND WAIFS AND STRAYS SOCIETY will shortly open a small children's Convalescent Home at Hurstpierpoint in a cottage offered rent-free by Mr. Worthington Church. At a recent meeting of the POOR CLERGY RELIEF CORPORATION the sum of £500 was distributed among clergymen, widows, and orphan daughters. To help sick and overworked clergymen to take holidays, grants to the amount of £205 were also made. HOSPITAL SUNDAY FUND.— At a meeting of the Council held recently at the Mansion House, awards were made to 157 hospitals and 58 dispensaries of the available sum of £56,371. The total received is £60,000, or £5,000 less than last year, an encouraging amount considering the general lack of ready money. No grant has been made to the City Orthopaedic Hospital, which was advised to amalgamate with other similar institutions. 378/IMSW/A/1/1/39